The Many Faces of Mimesis Selected Essays from the 2017 Symposium on the Hellenic Heritage of Western Greece - Reid, Heather L. (Heritage of Western Greece, 2018)
Mimesis can refer to imitation, emulation, representation, or reenactment - and it is a concept that links together many aspects of ancient Greek Culture. The Western Greek bell-krater on the cover, for example, is painted with a scene from a phlyax play with performers imitating mythical characters drawn from poetry, which also represent collective cultural beliefs and practices. One figure is shown playing a flute, the music from which might imitate nature, or represent deeper truths of the cosmos based upon Pythagorean views (which were widespread in Western Greece at the time). The idea that mimesis should be restricted to ideals was made famous by Plato (whose connections to Pythagoreanism and Siracusa are well-known), and famously challenged by his student Aristotle (not to mention by the mimetic character of Plato's own poetry). This volume gathers essays not only on the philosophical debate about mimesis, but also on its use in architecture, drama, poetry, history, music, ritual, and visual art. The emphasis is on examples from Hellenic cities in Southern Italy and Sicily, but the insights apply far beyond - even to modern times.